Assessment of Water Quality of "Sakegaon Reservoir" Maharashtra - Agarkar, S.V. (Asian Journal of Chemistry, 2010)
The suitability of water for drinking and other domestic purposes is studied by collecting samples from Sakegaon reservoir situated in Chikhli area of Buldhana Distt. Maharashtra Samples were analysed -for physico-chemical parameters, The present paper reports a study on its water quality.